Sensibilidade à secagem da matéria-prima cerâmica da Formação Corumbataí na região do Polo Cerâmico de Santa Gertrudes, SP - Azzi, A. A. [UNESP]; Curtolo, M. Z. [UNESP]; Zanardo, A. [UNESP] (FapUNIFESP (SciELO), 2015)
The clays from the Corumbataí Formation are the major source of raw ceramic materials for industries in the Ceramic District of Santa Gertrudes, SP, Brazil. 73% of those industries that use the dry grinding process are being targeted of increasing pressure from the environmental control agencies due to particle emission (dust) in the air associated with the drying process of raw materials. In this paper, four different types of experiments were performed on three different types of raw-material (D, I and M) from the Corumbataí Formation, with initial moisture contents of 8%, 18%, 19%, respectively, to evaluate the drying sensitivity of these samples. The tests conducted were drying by sunlight, drying by wind, drying by sunlight combined with an air stream, and drying by sunlight the samples previously moistened in flowing water. The tests were correlated with thermogravimetric analyses. The X-ray diffraction analysis along with the chemical and petrographic analysis has shown that samples D, I and M contain, mainly, phyllosilicates 2:1, such as illite (25-30%) and smectite (15-25%), and fewer amounts of kaolinite (0-15%) and chlorite (0-5%). The results of the drying experiments associated with the mineralogy of the samples showed that the thermogravimetric curves in the 100 °C-200 °C range may indicate in a faster way the materials drying sensitivity, once the major moisture loss obtained in this range indicates the largest amount of smectite, which gives a lower drying sensitivity to the material. Moreover, the dry route procedures suggest that drying the materials separately may improve the drying process results.
Raw ceramic material drying sensitivity from Corumbataí Formation in the Ceramic District of Santa Gertrudes, SP, Brazil
Keywords: Ceramic District of Santa Gertrudes; Clays; Corumbataí Formation; Drying; Raw ceramic material